Dislocation network in additive manufactured steel breaks strength–ductility trade-off. Issue 4 (May 2018) - Liu, Leifeng; Ding, Qingqing; Zhong, Yuan; Zou, Ji; Wu, Jing; Chiu, Yu-Lung; Li, Jixue; Zhang, Ze; Yu, Qian; Shen, Zhijian
Graphical abstract: Abstract: Most mechanisms used for strengthening crystalline materials, e.g. introducing crystalline interfaces, lead to the reduction of ductility. An additive manufacturing process – selective laser melting breaks this trade-off by introducing dislocation network, which produces a stainless steel with both significantly enhanced strength and ductility. Systematic electron microscopy characterization reveals that the pre-existing dislocation network, which maintains its configuration during the entire plastic deformation, is an ideal "modulator" that is able to slow down but not entirely block the dislocation motion. It also promotes the formation of a high density of nano-twins during plastic deformation. This finding paves the way for developing high performance metals by tailoring the microstructure through additive manufacturing processes.